Chicken antibodies are highly suitable for particle enhanced turbidimetric assays - Larsson, Anders; Campbell, Andrew; Eriksson, Mats (Frontiers in Immunology, 2022)
Antibody-based assays are commonly used in clinical laboratories for analyzing plasma, serum and other samples for particular protein markers. Although such assays have been traditionally based on antibodies raised in mammals (e.g., mice, rabbits, goats), there are several advantages of using avian antibodies (IgY) raised in chickens, including production volumes, costs, and ethical/animal welfare considerations. A further disadvantage of using mammalian IgG in such assays is the potential for agglutination when exposed to rheumatoid factor (RF) in serum. However, when used in the free form the immune complexes formed with avian antibodies have been reported to have less ability than those formed with mammalian antibodies to cause the light scatter which are used for instrument measurement. In addition, when the amount of antigen exceeds the maximum precipitating point in relation to the amount of antibody, there is a rapid decline in the absorbance values of the immune complexes (antigen excess) when IgY is used. However, when avian antibodies are conjugated to a substrate and used in particle enhanced turbidimetric assays (PETIA), these problems are avoided. Here we investigated three clinical assays using chicken antibodies, one using free (unbound) IgY and two with IgY-based PETIA. The IgY PETIA demonstrated a strong scatter response, even at high antigen concentrations in contrast to the steep decline seen with free IgY antibodies. IgY PETIA reagents can provide test results with low coefficient of variation (<1% for duplicate samples). We also investigated the effect of RF on agglutination of mammalian antibodies (IgG from mouse, rabbit, sheep, and human) and chicken antibodies. Whereas agglutination was observed with all the mammalian antibodies in the presence of RF, this was not observed at all with chicken IgY. Our results support the growing body of evidence that chicken egg yolks can thus be a valuable source of antibodies for use in PETIA in clinical laboratories.